Modelo para un plan estratégico en futuros reasentamientos (2021)
Currently, Colombia is in the first place in the world for the 4th consecutive year with the highest percentage of forced displacement, due to natural disasters, construction of hydroelectric plants and third-party conflicts. In the departments of Colombia, Huila is one of the areas most noted for having fixed sources of resettlement not only for environmental reasons but also for public constructions, a clear example is the construction of the Quimbo Dam, which was planned and built for a common good in the Department of Huila but which in turn caused different losses in the inhabitants who inhabited the area of influence, among these effects were the loss of 8,500 hectares of productive agricultural land, which generated the forced displacement and the breakdown of the social fabric among the affected population, in the face of this problem, a model is proposed for a strategic plan in future resettlements, which has the purpose of improving the quality of life of people by preventing the disarticulation of their social fabric and thus offering them better opportunities for lifetime.